Financing Constraints and Employers' Investment in Training - Giorgio Brunello; Áron Gereben; Christoph T. Weiss; Patricia Wruuck (Institute of Labor Economics (IZA), 2020)
Using a representative sample of European firms, we study whether and to what extent financing constraints affect employers' decision to invest in employee training. We combine survey data on investment activities with administrative data on financial statements to develop an index of financing constraints. We estimate that a 10 percent increase in this index reduces investment in training as a share of fixed assets by 2.9 to 4.5 percent and investment in training per employee by 1.8 to 2.5 percent. We document that lower investment in training reduces productivity, and show that firms facing tighter financing constraints cut back the investment in training and tangible assets less than the investment in R&D and software and data.
Keywords: J24; 330; training; financing constraints; Europe